Direct 3D printing of hiPSC-cardiomyocytes in collagen-based bioinks. (14th October 2021) - Esser, T U; Engel, F B
Abstract: Background: Cardiac tissue engineering is an effective strategy to generate tissues for drug testing and disease modelling as well as for cardiac repair. Tissues produced by casting show good functionality and advanced maturation, but do not replicate the native tissue architecture and hierarchy. Additive manufacturing technologies, such as 3D bioprinting, enable the generation of hierarchically structured tissues with complex geometries. This technology has been used previously to generate models of the heart. However, these approaches either showed limited tissue functionality or required a two-step procedure using a structural and a cell-laden bioink. Purpose: Here, we aimed to develop a collagen-based bioink, which enables direct 3D-bioprinting of hiPSC-derived cardiomyocytes and supports the formation of functional cardiac tissue. Methods: To generate cardiac tissues, a commercial pneumatic extrusion bioprinter with custom modifications to enable passive cooling of the bioink was used. Gelatin/gum arabic microparticles were obtained through complex coacervation, compacted by centrifugation and utilized as support bath. Cardiomyocytes were differentiated in 2D monolayer and expanded by CHIR99021-treatment and regular passaging. Cells were encapsulated in a rat collagen-I based bioink and printed into support bath prior to gelation. After bioink gelation at 37°C, support bath was removed, and constructs cultivated free-floating for up to 30 days. Results: We printed ring-shaped cardiac tissues measuring 5 x 5 x 1 mm, which remained stable over the course of cultivation. First contractions were observed after three days, which increased in magnitude and synchronized across the tissue with prolonged culture. HiPSC-cardiomyocytes displayed striated sarcomeres and were responsive to pharmacological stimulation. In addition, using two distinct bioinks, multi-layered constructs were generated. Conclusion: 3D-bioprinting is a promising tool to generate engineered cardiac tissues with complex geometries and improved functionality through designed hierarchy. Our collagen-based bioink and associated printing strategy enables the fabrication of Collagen-based contractile cardiac tissues in a direct manner. FUNDunding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Deutsche Forschungsgemeinschaft (DFG)